2015
DOI: 10.15283/ijsc.2015.8.2.228
|View full text |Cite
|
Sign up to set email alerts
|

FGF8 is Essential for Functionality of Induced Neural Precursor Cell-derived Dopaminergic Neurons

Abstract: Induced neural precursor cells (iNPCs) are one source of transplantable dopaminergic neurons used in cell therapy for Parkinson’s disease. In the present study, we demonstrate that iNPCs can be generated by transducing Brn2, Ascl1, Myt1L and Bcl-xL in a culture supplemented with several mitogens and subsequently can be differentiated to dopaminergic neurons (DA). However, studies have shown that iDA and/or iNPC-derived DA neurons using various conversion protocols have low efficiency. Here, we show that early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…This approach includes trans-differentiation to a desired cell type from autologous cells ( Graf and Enver, 2009 ; Lee et al ., 2015 ). For example, many papers achieved trans-differentiation of fibroblasts to functional and specific cell types such as neurons, neural precursor cells (NPC), astrocytes, oligodendrocytes, cardiomyocytes, and hepatocytes ( Ieda et al ., 2010 ; Vierbuchen et al ., 2010 ; Sekiya and Suzuki, 2011 ; Caiazzo et al ., 2015 ; Lim et al ., 2015a , 2015b ; Prasad et al ., 2017 ). Important factors in trans-differentiation include the efficiency of reprogramming and suitability for experimental implementation.…”
Section: Introductionmentioning
confidence: 99%
“…This approach includes trans-differentiation to a desired cell type from autologous cells ( Graf and Enver, 2009 ; Lee et al ., 2015 ). For example, many papers achieved trans-differentiation of fibroblasts to functional and specific cell types such as neurons, neural precursor cells (NPC), astrocytes, oligodendrocytes, cardiomyocytes, and hepatocytes ( Ieda et al ., 2010 ; Vierbuchen et al ., 2010 ; Sekiya and Suzuki, 2011 ; Caiazzo et al ., 2015 ; Lim et al ., 2015a , 2015b ; Prasad et al ., 2017 ). Important factors in trans-differentiation include the efficiency of reprogramming and suitability for experimental implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Data are expressed as mean±SEM. When more than two groups were compared, a paired t -test was performed using SigmaPlot for Windows, version 10.0 (Systat Software GmbH, Erkrath, Germany) (5).…”
Section: Methodsmentioning
confidence: 99%
“…The direct differentiation of somatic cells into tissuespecific cells such as induced neurons (1) and neural precursor cells (25) may serve as an attractive approach in the field of stem cell research. The first study in this direction was reported by Vierbuchen et al (1) using neuronal lineage-inducing transcription factors such as Brn2 , Ascl1 , and Myt1L (BAM).…”
Section: Introductionmentioning
confidence: 99%
“…FGF-8 is also a promising candidate for the treatment of neurodegenerative diseases, where it has broad activity in neural tissue and is vital in promoting dopaminergic neuron development and function ( Chen et al, 2016 ). FGF-8 can induce dopaminergic neuronal differentiation and promote dopaminergic axons’ growth in the midbrain by increasing Semaphorin 3F ( Yamauchi et al, 2009 ; Lim et al, 2015 ). Two major FGF-8 isoforms are expressed in the midbrain (FGF-8a and FGF-8b), whereas FGF-8 b promotes midbrain development, and FGF-8b is structurally similar to FGF-18 and has similar receptor-binding characteristics ( Liu et al, 2003 ).…”
Section: Fibroblast Growth Factor Plays An Essential Role In Protecting and Repairing Dopaminergic Neuronsmentioning
confidence: 99%